Effect of biaxial Tensile Loading Ratio (σx/σy) on Stress Distribution Around Crack Tip - Hassan, A. K. F.; Aziz, Ossama Abdul (Basrah Journal for Engineering Sciences, 2010)
This paper deals with the computer simulation of stress distribution in a plane model of mild steel under biaxial tensile loading. The goal is to visualize the crack behavior under deferent ratios of biaxial loading through linear elastic fracture mechanics theory. A finite element method is considered in calculating the mixed mode of stress intensity factor that governing the influence of stresses distribution around the crack. Aspects of crack propagation are considered. It is found that the mw.imum ci..-cumfcrcnce .stress is not of the plane of crack but that inclined by an angle (68) from it.